Japanese perceptions of societal vulnerability to disasters during population ageing: Constitution of a new scale and initial findings. (September 2016) - Annear, Michael J.; Otani, Junko; Gao, Xin; Keeling, Sally
Abstract: This research describes the development and initial results from the Perceptions of Ageing and Disaster Vulnerability Scale (PADVS) that was designed to explore perceptions of vulnerability to disasters in the context of population ageing. Few Japanese studies have explored perceptions of disaster-related vulnerability in Japan, although this issue is growing in importance due to the acceleration of population ageing and the recurrence of large-scale disasters. Following pre-testing, the PADVS was administered with 172 health students and professionals from three Japanese regions in 2016. The reliability and validity of the PADVS were assessed using commonly employed psychometric evaluation techniques, including assessment of face and content validity, internal consistency, item-total correlations, inter-item correlations, and factorial validity. Descriptive statistics were used to ascertain total, subscale, and item scores. With one item removed due to poor fit, a 13-item version of PADVS exhibited acceptable reliability (α=.87) and validity. The scale fit a four-component solution following principal components analysis, with four indicative subscales. Results of PADVS completion showed clear respondent concerns about social isolation and lack of support networks, and poor functional capacity among older adult populations. The PADVS provides a reliable and valid measure for researchers to assess perceptions of societal vulnerability related to disasters in the context of population ageing. Preparations for recurring disasters should focus on improving supportive social network connections among older adults and providing intervention measures to improve physical, cognitive, and emotional health for older adults, particularly those who live alone in the community. Highlights: Population ageing in Japan may increase vulnerability to disasters. The Perceptions of Ageing and Disaster Vulnerability Scale is a reliable and valid measure. Social isolation and functional declines are perceived as major vulnerabilities. Current perceived vulnerabilities among older Japanese are amenable to intervention.